The role of reading skills in statistical literacy among bilingual and native Hebrew-speaking college students. Issue 9 (21st October 2022) - Sarid, Miriam; Vaknin-Nusbaum, Vered; Abbas, Randa; Dardick, William
ABSTRACT: The aim of the current study was to examine the relations between reading literacy and statistical literacy of Hebrew-speaking college students (L1) compared with Arabic-speaking students whose second language (L2) is Hebrew. The contribution of reading skills to statistical literacy in L1 and L2 students and the differences between the groups, were examined. Statistical literacy was tested via final grades in the statistics class. Forty-six native Hebrew speakers and 30 Arabic-speaking college students participated in the study. Word recognition and working memory predicted statistical literacy of both groups, and slower speed of decoding new words predicted better statistical literacy of L2 readers. This is a pioneering study that explores the contribution of reading skills to statistical literacy among L1 and L2 college students. The findings reveal the critical reading skills needed for statistical literacy. This study may enable educators to better assist college students in developing statistical literacy.